Thermal and electrical performance evaluations of series connected Li-ion batteries in a pack with liquid cooling. (25th January 2018) - Malik, M.; Dincer, I.; Rosen, Marc A.; Mathew, M.; Fowler, M.
Highlights: Li-ion battery pack testing at 1C, 2C, 3C, 4C and drive cycle with liquid cooling. Three 20Ah LiFePO4 cells connected in series tested with coolant at 10–40 °C. Battery pack temperature remains in required range (25–40 °C) with coolant at 30 °C. The maximum rise in battery pack temperature in only 1.1 °C with drive cycle. Energy efficiency and exergy destruction increase with rise in coolant temperature. Abstract: Lithium-ion batteries are widely used in electric and hybrid electric vehicles due to their wide nominal range and high power densities. However, operating temperature, which has a pronounced effect on battery thermal performance and electrical performance, needs to be maintained within a specified range. In the present study, a Li-ion battery pack has been tested under constant current discharge rates (e.g. 1C, 2C, 3C, 4C) and for a real drive cycle with liquid cooling. The experiments are performed using cold plates at 10 °C, 20 °C, 30 °C, and 40 °C coolant temperatures to obtain thermal and electrical parameters. For this, three 20Ah LiFePO4 prismatic cells are connected in series and a battery thermal management system is designed and developed for liquid cooling. To measure the temperature variation, 18 thermocouples are installed on the principal surface of all three cells: i.e., six on each cell. The results show that the battery pack temperature can be maintained within the required range at all four selected discharge rates with the coolant at 30 °C. The discharge capacity of the battery pack increases with increasing coolant temperature and is found to achieve a maximum of 19.11 Ah at a 1C discharge rate with the coolant at 40 °C.